First record of freshwater shrimp, Macrobrachium lamarrei lamarrei (H. Milne Edwards, 1837) from Gujarat, India - Barkha Purohit (Journal of Fisheries, 2018)
In the present study the presence of freshwater shrimp Macrobrachium lamarrei lamarrei (H. Milne Edwards, 1837) was recorded for the first time from a freshwater pond of Dabhoi, Vadodara district of Gujarat State, India in March 2015. This report discusses the taxonomy and distribution of this species.